DEVELOPMENT OF LEAN ENTERPRISE IMPLEMENTATION METHODOLOGY: AN ISM APPROACH (KASBIT Business Journal, 2022)
In the current competitive environment, most manufacturing companies are looking to improve their competitiveness. They must embrace and apply industry best practices to strengthen their competitive edge. The adoption of new manufacturing best practices typically comes with the expectation of certain advantages in the form of improved organizational performance. The amount of time and attention put into adopting any best practices will result in improvements in many elements of the company. The researcher backed up the previous claim, stating, "The end objective of an organization's management techniques is to raise the level of performance." Lean Management (LM) is regarded as a best practice that consistently changes an organization from its worst to its best condition, which is the desired state for every business.
Keywords: Lean Management; Methodology; Manufacturing; Performance